Biomechanical Aspects of Shoulder and Hip Articulations: A Comparison of Two Ball and Socket Joints - Mustafa Qusay Ismael (Al-Khwarizmi College of Engineering – University of Baghdad, 2006)
The shoulder and hip joints though essentially both are ball and socket joints, show structural variability to serve functional needs.study aims at revealing some of the structural and functional properties of each of the two joints regarding the factors that contribute to the stability of any joint in the body, namely: bone, ligament, and muscleTwenty dried scapula, hip, humerus, and femur were used. The area of the articular surfaces was estimated by molding a sheet of dental wax. Using special graphics software, a novel procedure was described to calculate the area under the curve, which was postulated to indicate the degree of curvature. Tension test was applied using a testometric machine, which was locally modified to suit biological specimens. A finite element analysis was designed to study the articulating bones under different loading conditionsIn the hip joint, the area of the articular surface of the head of the femur and that of the lunate showed no significant statistical difference. For the shoulder joint, the articular areas of the head of the humerus and the glenoid were statistically different. No statistical significance was observed regarding curvature of the articular surfaces within both the hip and shoulder joints; however, the values were significantly different between the hip and shoulder. In the tension test, the site of rupture of the capsule of the shoulder joint was found to be at its anteroinferior part. The more contact between the area of the cup and ball, as was demonstrated in the hip joint, the more stable the joint. On the contrary, the shoulder articular surfaces have less area of contact, which makes it more mobile and decreases stability. The insignificant difference in curvature within both joints indicates a good congruity and thus more stability especially during joint movement. The curvature difference between the head of femur and the head of humerus indicates that the range of motion is quite different for the two joints. Results obtained from the finite element analysis were important in understanding the areas of stress concentration and were thoroughly explained from the anatomical point of view and linked to muscle and joint capsule attachments. The model of the joints developed in this study can be used as a computational tool to joint biomechanics and to prosthetic implant analysis. Keywords: hip joint, shoulder joint, finite element analysis, biomechanics.